Book Reviews (International review of mission, 1985)
Book reviewed in this article: IMPLICATIONS OF INTERFAITH DIALOGUE FOR CHRISTIAN THEOLOGY: No Other Name? A Critical Survey of Christian Attitudes Toward the World Religions, by Paul F. Knitter. IMPLICATIONS OF INTERFAITH DIALOGUE FOR CHRISTIAN THEOLOGY: Beyond Dialogue. Toward a Mutual Transformation of Christianity and Buddhism, by John B. Cobb, Jr. IMPLICATIONS OF INTERFAITH DIALOGUE FOR CHRISTIAN THEOLOGY: A Christian Theology of the People Israel, by Paul M. van Buren. LIBERATION THEOLOGY UNDER ATTACK: The True Church and the Poor, by Jon Sobrino. LIBERATION THEOLOGY UNDER ATTACK: Saint Francis: A Model for Human Liberation, by Leonardo Boff. LIBERATION THEOLOGY UNDER ATTACK: Salvation and Liberation: In Search of a Balance between Faith and Politics, by Leonardo and Clodovis Boff. LIBERATION THEOLOGY UNDER ATTACK: Church: Charism and Power: Liberation Theology and the Institutional Church, by Leonardo Boff. THE CHURCH IN NORTH AFRICA: L'Eglise d'Afrique du Nord du IIe au XIIe siècle, by Joseph Cuoq. THE CHURCH IN NORTH AFRICA: Le Cardinal Duval “Evêque en Algérie,” entretiens du Cardinal Léon-Etienne Duval avec Marie-Christine Ray. THE CHURCH IN NORTH AFRICA: Eglise en Islam: méditation sur l'existence chrétienne en Algérie, by Henri Teissier. MISSION IN BIBLICAL PERSPECTIVE: God Who Sends, by Francis M. DuBose MISSION IN BIBLICAL PERSPECTIVE: A Sense of Mission: Guidance from the Gospel of John, by Albert Curry Winn MISSION IN BIBLICAL PERSPECTIVE: Wie mich der Vater gesandt hat, so sende ich euch: Beiträge zur Tehologie der Sen-dung, edited by Heinrich M. Köster and Manfred Probst MISSION IN BIBLICAL PERSPECTIVE: The Biblical Foundations for Mission, by Donald Senior, C. P., and Carroll Stuhlmueller, C. P., Maryknoll MISSION IN BIBLICAL PERSPECTIVE: Mission im Neuen Testament, edited by Karl Kertelge, Freiburg MISSION IN BIBLICAL PERSPECTIVE: Turning the Church Inside Out, by Harold H. Rowdon MISSION IN BIBLICAL PERSPECTIVE: Fides pro mundi vita: Missionstheologie heute — Hans-Werner Gensichen zum 65. Geburstag, edited by Theo Sundermeier